Rheological and structural characterization of acidified skim milks and infant formulae made from cow and goat milk. (November 2019) - Wang, Yiran; Eastwood, Brooke; Yang, Zhi; de Campo, Liliana; Knott, Robert; Prosser, Colin; Carpenter, Elizabeth; Hemar, Yacine
Abstract: In this study, the viscoelastic properties of goat and cow skim milks and infant formula gels induced by acidification using Glucono- δ -Lactone (GDL) were investigated by small and large deformation rheology. The microstructures of the gels were characterized via the combination of confocal laser scanning microscopy (CLSM), ultra-small angle neutron scattering (USANS), small angle neutron scattering (SANS), and small angle X-ray scattering (SAXS). Compared to cow infant formula gels, goat infant formula gels displayed a lower elasticity and breaking stress. Similar differences were also observed in the gels of skim goat milk and skim cow milk. Moreover, for an infant formula from the same animal species, the one with a higher casein to whey ratio exhibited a stronger mechanical gel network. CLSM observations and USANS-SANS analysis indicated that thinner protein strands and more open protein networks with higher porosity were formed in the goat milk gels than in the cow milk gels, confirming the rheological findings. Finally, SAXS revealed that the internal structure of casein micelles from goat and cow milk are different and that as expected the calcium phosphate nanoclusters (CCP) are solubilized upon acidification. The observed differences in mechanical and microstructural properties may impact the digestive behavior, as reported in previous studies. Graphical abstract: Ultra-small angle neutron scattering (USANS) patterns of acid-induced bovine and goat infant formula (IF) gels with confocal laser scanning micrographs inserted.Image 1 Highlights: Cow and goat skim milk and infant formulae gels have different mechanical behavior. Cow milk gels have stronger gel strength and denser structure than goat milk gels. A higher casein to whey ratio exhibits a stronger milk mechanical gel network. USANS was firstly used to probe the microstructure of infant formula milk gels.